THE THEORY OF INTERSUBJECTIVITY IN THE WORK OF ALFRED SCHUTZ - SILAGHI, Raluca Marinela (Studia Universitatis Babeș-Bolyai Philosophia, 2017)
The Theory of Intersubjectivity in the Work of Alfred Schutz. The world of daily life is based on intersubjectivity, on the daily social interactions of the members of the community who live in common, each besides the others, undertaking a multitude of meaningful inter-relating activities sharing in the same time (the living present) and space. The intersubjectivity of the social world is built together with and for the others, whom I may effectively know by directly interacting with them, or whom I may not know at all. My relationship with these others may be of different degrees of closeness (when my experience of another is of a We-type relationship) or of foreignness (when my experience of my contemporary is of a They-type relationship).I’m directly experiencing the other, having immediate access to his subjectivity when we are engaged in a face-to-face interaction, which requires that we share a common sector of space and time.